Transgenic Arabidopsis thaliana containing increased levels of ATP and sucrose is more susceptible to Pseudomonas syringae - Zhang, Renshan (PLoS One, 2017)
Disease resistance exerts a fitness cost on plants, presumably due to the extra consumption of energy and carbon. In this study, we examined whether transgenic Arabidopsis thaliana with increased levels of ATP and sucrose is more resistant or susceptible to pathogen infection. Lines of A. thaliana over-expressing purple acid phosphatase 2 (AtPAP2) (OE lines) contain increased levels of ATP and sucrose, with improved growth rate and seed production. Compared to wild type (WT) and pap2 lines, the OE lines were more susceptible to several Pseudomonas syringae pv. tomato (Pst) strains carrying AvrRpm1, AvrRpt2 AvrRps4, AvrPtoB, HrcC and WT strain DC3000. The increased susceptibility of the OE lines to Pst strains cannot solely be attributed to the suppressed expression of R-genes but must also be attributed to the suppression of downstream signaling components, such as MOS2, EDS1 and EDS5. Before infection, the levels of salicylic acid (SA) and jasmonic acid (JA) precursor OPDA were similar in the leaves of OE, pap2 and WT plants, whereas the levels of JA and its derivative JA-Ile were significantly lower in the leaves of OE lines and higher in the pap2 line. The expression of JA marker defense gene PDF1.2 was up-regulated in the OE lines compared to the WT prior to Pst DC3000 infection, but its expression was lower in the OE lines after infection. In summary, high fitness Arabidopsis thaliana exhibited altered JA metabolism and broad suppression of R-genes and downstream genes as well as a higher susceptibility to Pst infections.